2013
DOI: 10.5114/pwki.2013.38863
|View full text |Cite
|
Sign up to set email alerts
|

s Relationship between SYNTAX score and Trans-Atlantic Inter-Society Consensus II classification in patients undergoing diagnostic angiography

Abstract: IntroductionPeripheral artery disease (PAD) is a marker of systemic atherosclerosis and most patients with PAD also have concomitant coronary artery disease (CAD).AimThere are no published data investigating the relationship between PAD and CAD complexity assessed by a well-accepted classification system such as the SYNTAX score (SS) or Trans-Atlantic Inter-Society Consensus II (TASC II).Material and methodsThe study population consisted of 72 patients who underwent coronary angiography for the assessment of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Nevertheless, Marchant et al ( 24 ) suggested that the SCORE model should be preferred to the Framingham model to predict the risk cardiovascular death in a French population. Erkan et al ( 25 ) evaluated the association between peripheral artery disease and coronary artery disease considering two interventional score models such as the SYNTAX score and Trans-Atlantic Inter-Society Consensus II classification. In the current study, we evaluated the reliability and applicability of the two risk stratification models in deference to the SYNTAX score.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Marchant et al ( 24 ) suggested that the SCORE model should be preferred to the Framingham model to predict the risk cardiovascular death in a French population. Erkan et al ( 25 ) evaluated the association between peripheral artery disease and coronary artery disease considering two interventional score models such as the SYNTAX score and Trans-Atlantic Inter-Society Consensus II classification. In the current study, we evaluated the reliability and applicability of the two risk stratification models in deference to the SYNTAX score.…”
Section: Discussionmentioning
confidence: 99%
“…The determination of which lower limb arterial segment critical stenosis is the most predictive arterial zone for estimating severe CAD was also sought. Although there are few studies in this regard, they have been conducted by evaluating only the aortoiliac segment via Trans-Atlantic Inter-Society Consensus (TASC) II classification and the extent of CAD was only evaluated using the Syntax score [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In a Swedish observational study, the Cox proportional hazard model revealed an almost doubled 10-year risk of CV mortality in asymptomatic patients (HR 1.9), an HR of 2.6 in patients with intermittent claudication (IC) and an HR of 3.5 in patients with severe limb ischemia [ 18 ]. LE-PAD and its severity also predict the extension and complexity of CAD: ABI can be employed as a useful predictor for CAD complexity assessed by SYNTAX Score [ 19 ], and a higher Trans-Atlantic Inter-Society Consensus II classification is also associated with a higher SYNTAX Score [ 20 ].…”
Section: Epidemiology and Prognosismentioning
confidence: 99%